Land Potential Analysis for Health Service Facilities (Puskesmas) in the Pinangsia Village, DKI Jakarta Province - Prama Ardha Aryaguna, S.Si., M.Sc.; Horas Maulite Andrey Gromiko; Dayu Ariesta Kirana (JPG (Jurnal Pendidikan Geografi), 2023)
Provision of Health Facilities is one of the government's mandates in ensuring public health in accordance with the 1945 Constitution article 34 paragraph 3 "The state is responsible for the provision of proper health service facilities and public service facilities" and Law No. 36 of 2009 article 15. Based on data from the Health Service it shows there are still health service facilities that operate not on land owned by the Provincial Government of DKI Jakarta. Government health services located on land with a lease or contract mechanism are very prone to experiencing problems such as contract extensions, permits, etc. Through a geographic information system, a model of the priority locations for the procurement of health services was developed to become a recommendation for the DKI Jakarta government. Based on the results of the analysis, the number of potential parcels obtained is 23 potential parcels which are dominated by potential parcels with priority category 2 with a total of 16 parcels, followed by priority category 1 with a total of 7 parcels